Research on Tourism, Indigenous Peoples and Economic Development: A Missing Component - Richard Butler (Land, 2021)
Indigenous tourism is a term commonly used to describe tourism that involves indigenous peoples or first nations in tourism. In recent years, research attention on this topic has broadened and expanded greatly, reflecting both increased involvement of indigenous peoples and their more active participation in controlling and utilising a widening range of tourism and economic development. This more active participation has taken tourism beyond its traditional role as a limited source of employment and economic development to a stage at which tourism is being utilised as an agent to improve the indigenous political position with respect to controlling a wider range of development and strengthening regional and national identities. The paper briefly reviews research on indigenous tourism over the past half-century, noting the increase in volume and the changing nature and role of research on tourism involving indigenous peoples, but also longstanding neglect of some elements of economic development, which are discussed in more detail It also explores current and likely future issues needing research attention in the light of changing motivations for participation in indigenous tourism, and the spread of indigenous tourism beyond traditional areas into activities more associated with metropolitan and mass tourist markets.